Individual Sweet Taste Perception Influences Salivary Characteristics After Orosensory Stimulation With Sucrose and Noncaloric Sweeteners - Karl, Corinna M.; Vidakovic, Ana; Pjevac, Petra; Hausmann, Bela; Schleining, Gerhard; Ley, Jakob P.; Berry, David; Hans, Joachim; Wendelin, Martin; König, Jürgen; Somoza, Veronika; Lieder, Barbara (Frontiers in Nutrition, 2022)
Emerging evidence suggests a major role for salivary flow and the viscoelastic properties for taste perception and mouthfeel. Sweet-tasting compounds have also been proposed to have an effect on salivary characteristic. However, it is yet not clarified if perceived differences in the sensorial properties of structural diverse sweet tasting compounds contribute to salivary flow and viscoelasticity of saliva as part of mouthfeel and overall taste perception. Here we hypothesized that sensorially diverse sweeteners would affect salivary characteristics differently. Thus, we investigated the salivary flow, viscoelasticity of saliva, and selected influencing factors including the basal oral microbiome from 21 healthy test subjects after orosensory stimulation with sucrose, rebaudioside M (RebM), sucralose, and neohesperidin dihydrochalcone (NHDC) in a cross-over design. All test compounds enhanced the salivary flow by up to 1.51 ± 0.12 g/min for RebM, compared to 1.10 ± 0.09 g/min for water in the first minute after stimulation. The increase in the flow rate was correlated moderately to the individual perceived sweetness (r= 0.3, p< 0.01), but did not differ between the test compounds. The complex viscosity of the saliva was not affected by the test compounds, but analysis of covariance showed that the complex viscosity was associated (p< 0.05) with the concentration of mucin 5B (Muc5B). The oral microbiome showed a typical composition and diversity but was strongly individual-dependent (PERMANOVA: R²=0.76, p< 0.001), and was not associated with the changes in salivary characteristics. In conclusion, the present study indicates an impact of the individual sweetness impression on the flow rate without measurable changes in the complex viscosity of saliva, which may contribute to overall taste perception and mouthfeel of sweet tasting compounds.